Biodiversity and abundance of Planktonic Cnidaria (Siphonophorae ) in Lattakia Port - Durgham, Hani; Ikhtiyar, samar; Ibraheem, reem (Latakia University Journal -Biological Sciences Series, 2019)
نعرض في هذا البحث دراسة أولية للقراصيات البلانكتونية (رتبة الإنبوبيات) في منطقة الميناء التجاري بمدينة اللاذقية خلال الفترة مابين تشرين الثاني 2013 وحتى آب 2014. حُدد 9 أنواع من الأنبوبيات ظهرت معظمها خلال شهر شباط (2014) , نذكر منها الأنواع الأكثر سيطرة وهي: Eodoxoides spiralis يليه النوع Bassia bassensis, ثم النوع Chelophyes contorta وهو أحد الأنواع الأقل غزارة ويسجل لأول مرة في المياه الشاطئية السورية. سجلت الغزارة العظمى للقراصيات خلال شهر أيار حيث بلغ متوسط الغزارة 130 فرد/100م3 شكلت الأنبوبيات حوالي 98% من هذه الغزارة و أقلها في شهر آب وكان 1 فرد/100م3 ,حيث سجلت أعلى غزارة للأنبوبيات في أيار (426 فرد/100م3 ) وذلك في المحطة الثانية St2 . كانت المحطة الثانية St.2 (البعيدة عن مصادر التلوث) الأكثر تنوعاً و غزارةً بالأنبوبيات بين المحطات الأربعة المدروسة, بينما كانت المحطة الأولى St.1 (المعرضة مباشرة للتلوث) الأقل غزارةً وتنوعاً. In this paper the preliminary study were conducted on the Cnidaria (Siphonophorae) in the Commercial port of Latakia city between November 2013 and August 2014. Nine species of Siphonophorae were identified, most of them listed during February 2014. The most abundant species are : Eodoxoides spiralis and Bassia bassensis ; Chelophyes contorta is the lowest abundance species and were recorded for the first time in Syrian costal water. The highest abundance of Cnidaria were recorded during May with average 130 ind./100m3 , 98% of this average belong to Siphonophorae , whereas the lowest abundance recorded at August (1 ind./ 100m3) , in May the highest abundance of Siphonophorae (426 individual / 100 m3) in the station St2 were recorded. The most diverse and abundance station was St.2 (Far off the pollution source ) , while the station St.1(Exposed to direct pollution) was least in abundance and diversity of siphonophorae.